The Effectiveness of Reproductive Health Education in Reducing Fear of Pregnancy in Women of Childbearing Age - Abimulyani, Yumi; Mansyur, Tri Novianty; Siregar, Neny San Agustina; Widyawati, Widyawati (Oshada, 2025)
This study aims to analyze the effectiveness of reproductive health education in reducing fear of pregnancy among women of childbearing age through a qualitative approach based on literature review. Reproductive education is seen as a strategic instrument for improving reproductive literacy, strengthening self-efficacy, and correcting irrational perceptions of pregnancy risks. The literature review shows that women with high reproductive literacy tend to have a better scientific understanding of the reproductive system, enabling them to objectively assess pregnancy risks and reduce unfounded anxiety. Effective educational programs focus not only on knowledge transfer but also on psychological strengthening and social empowerment. Sociocultural factors, educational communication, and gender relations have been shown to be important determinants in the successful internalization of educational messages. Education that is sensitive to cultural values and participatory in nature can build trust, increase acceptance of the material, and expand the program's influence on the behavioral and emotional domains. The synthesis of results shows that comprehensively designed reproductive health education contributes significantly to reducing fear of pregnancy through the integration of cognitive, affective, and social aspects. These findings emphasize the importance of a multidimensional approach in reproductive health interventions to achieve a balance between scientific understanding and psychological well-being for women of childbearing age.